2015
DOI: 10.4238/2015.december.23.18
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of ADP-glucose pyrophosphorylase small subunit gene in Cyperus esculentus (yellow nutsedge)

Abstract: ABSTRACT. ADP-glucose pyrophosphorylase (ADPGlcPPase) controls the first committed step of starch synthesis by catalyzing the biosynthesis of ADP-glucose from glucose-phosphate and ATP. It is a tetrameric protein consisting of two small and two large subunits. The small subunits have a catalytic function, while the large subunits regulate the enzyme activity. Cyperus esculentus (yellow nutsedge) is a perennial C 4 plant grown from rhizomes and tubers. Previous studies on yellow nutsedge have mostly focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The yellow nutsedge tubers were germinated at 22 °C under a 16 h light/8 h dark cycle. RNA was isolated from leaves, roots and fresh tubers as described by Cheng et al [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…The yellow nutsedge tubers were germinated at 22 °C under a 16 h light/8 h dark cycle. RNA was isolated from leaves, roots and fresh tubers as described by Cheng et al [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…41 A lot of factors decide the amylose content of TNS, including genotypes, growing conditions and agronomic practices. 1,42 Because TNS is one of relatively less known and underutilized starch sources, there is little known about other components in TNS, such as lipids, proteins, minerals and phytochemicals, which is of common occurrence in other tuber starches. 43,44 3.2 Granular structure…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In monocots, AGPase comprises two large subunits and two small subunits, which interact and polymerize into the native heterotetrameric enzyme structure [21,22]. The small subunit is the catalytic center of the enzyme and the key site for enzyme allosteric effects [23]. The two subunits are encoded by different genes and studies of Arabidopsis have shown that they are functionally interdependent.…”
Section: Starch and Sucrose Metabolism Affected Stamen Developmentmentioning
confidence: 99%